Modulation of the inflammatory response of bovine mammary epithelial cells by cholecalciferol (vitamin D) during Staphylococcus aureus internalization - Alva-Murillo, Nayeli; Téllez-Pérez, Ana Dolores; Medina-Estrada, Ivan; Álvarez-Aguilar, Cleto; Ochoa-Zarzosa, Alejandra; López-Meza, Joel E. (Microbial pathogenesis, 2014)
Vitamin D is an immunomodulator that exerts anti-inflammatory effects. In this work, the effects of cholecalciferol, a vitamin D precursor, on the inflammatory response of bovine mammary epithelial cells (bMECs) during the internalization of Staphylococcus aureus were analyzed. Cholecalciferol and S. aureus inhibited TLR2 mRNA expression, but cholecalciferol differentially modulated the TLR2 membrane abundance. In fact, 50 nM cholecalciferol inhibited the TLR2 membrane abundance in bMECs infected with S. aureus, and this concentration also exerted the highest inhibitory effect on internalization. Cholecalciferol down-regulated the mRNA expression of TNF-α and IL-1β and up-regulated that of RANTES and IL-10 but did not modify IL-6 and IL-8 expression. S. aureus strongly induced the mRNA expression of TNF-α, RANTES and IL-10 and inhibited IL-8 expression. Interestingly, cholecalciferol pre-treatments inhibited the bacterial-induced expression of TNF-α, IL-1β, RANTES and IL-10. In conclusion, cholecalciferol differentially regulates the inflammatory response of bMECs during S. aureus internalization and may be an effective innate immunity modulator in mammary gland tissues. •Cholecalciferol as a regulator of inflammatory response in mammary epithelium during infection.•Staphylococcus aureus internalization is reduced by cholecalciferol in mammary epithelium.•The reduction in S. aureus internalization correlates with TLR2 membrane abundance.•Cholecalciferol inhibits the inflammatory response induced by S. aureus in mammary epithelium.